Daclatasvir and asunaprevir treatment in patients infected by genotype 1b of hepatitis C virus with no or subtle resistant associated substitutions (RAS) in NS5A‐Y93. Issue 4 (28th December 2017) - Ishigami, Masatoshi; Hayashi, Kazuhiko; Honda, Takashi; Kuzuya, Teiji; Ishizu, Yoji; Ishikawa, Tetsuya; Nakano, Isao; Urano, Fumihiro; Kumada, Takashi; Yoshioka, Kentaro; Hirooka, Yoshiki; Goto, Hidemi
Abstract : In this study, we investigated the real‐world data of the first approved interferon‐free regimen in Japan, daclatasvir and asunaprevir (DCV+ASV), in chronic hepatitis C patients infected HCV genotype 1b with no or subtle amount of baseline resistant associated substitutions (RAS). Among 924 patients registered in our multicenter study, 750 patients who were proven not to be infected with NS5A‐Y93H RAS by direct sequencing and to have no or subtle amount (less than 20%) of NS5A‐Y93H RAS by probe assays (Cycleave or PCR invader assay) were included in this study. We investigated the anti‐viral effect and factors associated with SVR12. In statistical analysis, P  < 0.05 was considered as significant. The SVR12 rate in this population was 92.1% (562/618). Factors associated with SVR12 were male (odds ratio: 2.128; 95%CI: 1.134‐4.000, P  = 0.019); lower serum γGTP (odds ratio: 1.007; 95%CI: 1.002‐1.012, P  = 0.006); lower HCV‐RNA (odds ratio: 1.848; 95%CI: 1.087‐3.145, P  = 0.023), and RVR (odds ratio: 6.250; 95%CI: 2.445‐15.873, P  < 0.001). No patients with γGTP ≧ 80 IU/L without RVR showed SVR12 (0/4, 0%) and one patients with γGTP ≧ 20‐< 80 IU/L and HCV‐RNA ≧ 6.5 logIU/mL without RVR (5/10, 50%) and two female patients with RVR but γGTP ≧ 80 IU/L and HCV‐RNA ≧ 6.5 logIU/mL (7/13, 53.8%) showed a low SVR12 rate. In the present study, we showed a good viral response with DCV‐ASV treatment and identified four predictive factors associated with SVR12. These four markers could be a good predictive markers for the viral effect of this treatment regimen in patients with no or subtle amount of RAS in NS5A‐Y93.